FRI0047 Treatment of rheumatoid vasculitis with infliximab. (1st June 2001) - Kayser, M; Unger, L; Nüblein, H
Abstract : Background: Rheumatoid vasculitis (RV) is a systemic late stage complication in patients with rheumatoid arthritis (RA). Despite cyclophosphamide (CYC) therapy which is the treatment of choice the prognosis is very poor and most patients die within two years. From our last ten patients with RV who had to be treated by CYC five patients had to stop therapy because of serious complications like infection orcardiac failure. Three patients refractory to CYC were treated with infliximab. A 48 year old male RA patient developed systemic vasculitis with a pericardial effusion, which did not respond to pulse corticosteroids, CYC or even to plasmapheresis. The only way to manage this life threatening condition was to drain the effusion continuously. Infliximab therapy at 3 mg/kg was initiated. The pericardial effusion as well as all other signs of the systemic vasculitis resolved within two weeks. The second patient, a 62 year old man who underwent abdominal surgery -retrospectively probably because of vasculitis- developed vasculitic skin ulcers on the scrotum, the lower legs and in the abdominal wound. Since CYC and methotrexate only lead to a partial remission, infliximab infusions were given. Again, the vasculitic lesions healed. The last case is a 58 year old woman with a more classic RV characterised by crural ulcers. After getting panmyelopathy caused by CYC, infliximab was given and the vasculitic features disappeared. No complications of infliximab therapy occurred although two patients had superinfected skin ulcers. Our cases show that infliximab is an effective salvage therapy in patients with RV refractory to even CYC. Given the toxicity and complication rate of CYC in this RA patient subset infliximab may well be considered as a first choice alternative to CYC. Objectives: Methods: Results: Conclusion: